Analisis Putusan Hakim dalam Kasus Perceraian Akibat Hukuman Penjara Suami (Perspektif Maqashid Syariah) - Syafitri, Nurlaili; Syafi'i, Alfan (El 'Ailaah, 2025)
Divorce is the dissolution of a marital bond, which results in the termination of the relationship between husband and wife. A divorce petition may be filed by both parties, whether the husband or the wife. When the wife initiates the divorce, it is referred to as cerai gugat, and when initiated by the husband, it is called cerai talak. Divorce can occur for various reasons, one of which is the husband‟s imprisonment. This study aims to examine the judgment in case Number 3539/Pdt.G/2019/PA.Sbr regarding a divorce caused by the husband's imprisonment, and to analyze this from the perspective of maqashid sharia.This research is a normative study using a qualitative method. Primary data were collected through interviews, while secondary data were gathered from documentation and various relevant literature sources. The collected data were then reduced, presented, and concluded using data analysis techniques.The results of the study show that in case Number 3539/Pdt.G/2019/PA.Sbr, concerning divorce due to the husband‟s imprisonment, the plaintiff (wife) filed for divorce at the Sumber Religious Court, Class 1A, due to frequent disputes and continuous arguments. These conflicts stemmed from the fact that the husband was a narcotics user, leading to his arrest by the Cirebon police and subsequent imprisonment.The panel of judge‟s in granting the divorce included the defendant‟s absence from the court sessions, fulfillment of the requirement to advise the plaintiff to maintain the marriage, the failure of the mediation process, corroboration of the witness statements with the evidence submitted by the plaintiff, and the ongoing disputes caused by the husband‟s drug use and imprisonment. The judge did not base the decision solely on the husband's imprisonment because his sentence was less than five years. According to Government Regulation Nomor 9 of 1974, divorce can be granted on the grounds of a spouse‟s imprisonment only if the sentence is five years or more. From the perspective of maqashid sharia, the decision of the Sumber Religious Court, Class 1A, in case Number 3539/Pdt.G/2019/PA.Sbr, is aligned with the principles of Maqashid Syariah, as it ensures the benefit of the plaintiff, particularly in terms of preserving religion (hifdz ad-din), life (hifdz an-nafs), intellect (hifdz al-„aql), and property (hifdz al-maal).